(untitled) (Scientific journal of the Fergana State University, 2026)
This article highlights that in every state, the wealth of the people determines the strength of its army. In order to conduct continuous and relentless military campaigns, economic support is essential. This is a universally acknowledged principle. From this perspective, when describing the military campaigns of the Manghit rulers in Muhammad Yaqub Bukhariy’s work, their efforts to unite the country and build a centralized state are accompanied by references to the nation’s economic capabilities. Today, this madrasa has been reconstructed and transformed into a pilgrimage site once again, following the initiative and directive of our President. We learn about the efforts made by Amir Shohmurod for the development of society. Specifically, the article analyzes how he successfully organized the system of waqf-a unique institution of that time-in order to ensure the regular payment of salaries and stipends to teachers (mudarris) and students working and studying in mosques and madrasas, as part of his broader plan to restore and maintain religious and educational institutions.